Investigating convergence of cardiac and behavioral indicators of distress during routine vaccinations over the second year of life. Issue 3 (11th October 2020) - Waxman, Jordana A.; DiLorenzo, Miranda G.; Pillai Riddell, Rebecca R.; Flora, David B.; Schmidt, Louis A.; Garfield, Hartley; Flanders, Daniel; Weinberg, Eitan; Savlov, Deena
Abstract: There is considerable variability regarding the convergence between behavioral and biological aspects of distress responses in toddlerhood, and little research has investigated the convergence of these measures in high distress. The aim of the current study was to describe patterns of distress responses to vaccinations as indexed by both pain‐related behavioral distress and heart rate (HR) at 12 and 18 months. Caregiver‐toddler dyads were part of an ongoing longitudinal cohort observed during 12‐ ( N = 158) and 18‐month ( N = 122) well‐baby vaccinations. Parallel‐process growth mixture models discerned two distinct groups at 12 months and three distinct groups at 18 months. All groups had comparable pain‐related behavioral distress and HR responses post‐vaccination, with most participants displaying high arousal and regulation to baseline levels following the vaccination. However, at 18 months, an important minority had a blunted response or did not regulate to a low level of distress by 3 min post‐needle. Post hoc analyses revealed that higher baseline pain‐related behavioral distress predicted membership in the majority groups at 12 and 18 months. These results highlight the developmental differences and variability in behavioral and cardiac indicators of distress regulation across the second year of life.